Pelaksanaan Tanggung Jawab Sosial Perusahaan Dalam Masa Pandemi COVID-19 Pada PT Semen Padang - Yoko Rasaki Rasaki; Wetria Fauzi; Tasman Tasman (Lareh Law Review, 2023)
Corporate Social Responsibility (CSR) has become an obligation for every company in the form of a Limited Liability Company which in the process uses Natural Resources in Indonesia, this is regulated in Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies and Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies, but during the COVID-19 Pandemic with the existence of Large-Scale Social Restrictions (PSBB) for industries and offices referring to Article 4 of Government Regulation Number 21 of 2020, the implementation of CSR for PT Semen Padang was not carried out properly. Based on Presidential Instruction Number 4 of 2020 concerning Refocusing Activities, Budget Reallocation, and Procurement of Goods and Services in the Context of Accelerating the Handling of Corona Virus Disease 19 (COVID-19), states that the use of existing budgets for activities that accelerate the handling of COVID-19. This resulted in the planning of CSR activities in the Company's Activity Budget Plan (RKAP) which had been approved through the General Meeting of Shareholders (GMS) experiencing changes. Based on this, the problem formulation in this study explains how the Implementation of Corporate Social Responsibility Activities during the COVID-19 Pandemic at PT Semen Padang, as well as knowing what obstacles there are in its implementation. The research method used is empirical legal research. The implementation of PT Semen Padang's CSR activities during the COVID-19 Pandemic, which is guided by the Regulation of the Minister of State-Owned Enterprises of the Republic of Indonesia number PER-05 / MBU / 04/2021, focuses its activities on providing assistance to the community from previously more in carrying out community empowerment activities directly in the field, while the obstacles experienced come from the budget, PSBB regulations and community dependence